Efficacy and tolerability of chemosaturation in patients with hepatic metastases from uveal melanoma. (May 2022) - Estler, Arne; Artzner, Christoph; Bitzer, Michael; Nikolaou, Konstantin; Hoffmann, Rüdiger; Hepp, Tobias; Hagen, Florian; Eigentler, Thomas; Forschner, Andrea; Grözinger, Gerd
Background: Patients with hepatic metastatic uveal melanoma still have a poor outcome. Purpose: To evaluate overall survival (OS), progression-free survival (PFS), and response predictors in these patients treated with chemosaturation by percutaneous hepatic perfusion with melphalan (CS-PHP). Material and Methods: Between June 2015 and March 2020, a total of 29 patients (median age 69.7 years; age range 30–81 years; 60% women; median BMI 25.7 kg/m 2 ; range 18.7–35.3kg/m 2 ; 1–6 procedures per patient) were treated with 53 CS-PHPs. All patients received cross-sectional imaging for initial and follow-up examinations. Baseline tumor load, extrahepatic tumor load, tumor response, PFS, and OS were assessed. Non-parametric statistics were used. Results: After the initial CS-PHP, a partial response was observed in 11 patients (41%), stable disease in 12 patients (44%) and progressive disease in 4 patients (15%); two patients died before the response was evaluated. After initial CS-PHP, median OS was 12.9 ± 7.4 months and median PFS was 7.1 ± 7.4 months. OS after one year was 50%. After the second CS-PHP, median PFS was 7.9 ± 5.7 months. Seven patients had a liver tumor burden >25%, associated with a significantly shorter OS (6.0 ± 2.4 vs. 14.1 ± 12.7 months; P  = 0.008). At the time of first CS-PHP, 41% (12/29) of the patients had extrahepatic metastases that did not affect OS (11.1 ± 8.4 months vs. 12.9 ± 13.6 months; P  = 0.66). Conclusion: CS-PHP is a safe and effective treatment for the hepatic metastatic uveal melanoma, especially for patients with a hepatic tumor burden <25%.